Social media influencers and their role in global crisis situations: Consumers’ reaction to different type of content during lockdown - Monteiro, Beatriz Pascoal Gaião Martins (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence